Baihu Jia Guizhi Decoction Improves Rheumatoid Arthritis Inflammation by Regulating Succinate/SUCNR1 Metabolic Signaling Pathway. (26th December 2019) - Chen, Huan; Pan, Ting; Liu, Panwang; Wang, Ping; Xu, Shijun
Abstract : Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovitis. Succinate is an inflammatory metabolic signal that exacerbates RA synovitis by activating succinate receptor 1 (SUCNR1) to amplify the release of IL-1 β . Thus, inhibition of succinate activation of SUCRN1 could be an effective method to inhibit the inflammation of RA. Baihu Jia Guizhi decoction (BHGZ), which is composed of Gypsum Fibrosum, Anemarrhena asphodeloides Bge., Cinnamomum cassia Presl., Glycyrrhiza uralensis Fisch., and Oryza sativa L., is a Traditional Chinese Medicine (TCM) prescription used to treat RA in clinic. In addition, TCM believes that damp and heat environment is one of the causes of RA. In this study, we tested the role of damp and heat environments in exacerbating RA inflammation and the anti-inflammatory effect of BHGZ, based on succinate/SUCNR1/IL-1 β pathway in the adjuvant arthritis (AA) model with damp and heat environment (AA + DHE). Results showed that paw swelling and synovial pathology were significantly increased in AA rats, and these results were aggravated by stimulation in damp and heat environment. BHGZ improved AA + DHE rats' paw swelling, synovial hyperplasia, and inflammatory cell infiltration and reduced IL-1 β . In addition, AA rats significantly increased the expression of SUCNR1, and the stimulation of damp and heat environment not only increased the expression of SUCNR1 but also promoted the accumulation of succinate. BHGZ simultaneously reduced the concentration of succinate and the expression of SUCNR1. Finally, SDH activity was decreased in AA rats and AA + DHE rats, while BHGZ increased SDH activity and then reduced succinate concentration. Therefore, we prove that damp and heat environment deteriorated the inflammation of RA which is the activation of succinate/SUCNR1 pathway, while BHGZ regulates SDH activity to reduce the accumulation of succinate and inhibit the activation of SUCNR1 that is the underlying mechanism of its treatment of RA.